Fabrication and Characterization of Electrospun Wool Keratin/Poly(vinyl alcohol) Blend Nanofibers - Shuai Li; Xu-Hong Yang (Advances in Materials Science and Engineering)
Wool keratin/poly(vinyl alcohol) (PVA) blend nanofibers were fabricated using the electrospinning method in formic acid solutions with different weight ratios of keratin to PVA. The resultant blend nanofibers were characterized by scanning electron microscopy (SEM), Fourier transform infrared (FTIR), X-ray diffraction (XRD), thermal gravimetric analysis (TGA), and tensile test. SEM images showed that the diameter of the blend nanofibers was affected by the content of keratin in blend solution. FTIR and XRD analyses data demonstrated that there were good interactions between keratin and PVA in the blended nanofibers caused by possibly hydrogen bonds. The TGA study revealed that the thermal stability of the blend nanofibers was between those of keratin and PVA. Tensile test indicated that the addition of PVA was able to improve the mechanical properties of the electrospun nanofibers.